THE EFFECT OF FIELD WORK PRACTICE AND CAREER GUIDANCE THROUGH SELF-EFFICACY ON STUDENTS' WORK READINESS - Muhammad Syibra Nizar Agha Zahirulhaq; Hengky Pramusinto (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: The high unemployment rate among SMK graduates, especially in Central Java, persists. A 2024 tracer study at SMK Swadaya Temanggung reveals that some graduates continue to experience unemployment and a skills mismatch. Purpose: To examine the influence of field work practice and career guidance on students' work readiness, with self-efficacy as a mediating variable. Novelty: This study emphasizes self-efficacy as a mediator, revealing both direct and indirect effects of fieldwork and career guidance on work readiness. Research Methods: Data were collected from students of class XII majoring in Office Management at SMK Swadaya Temanggung using questionnaires. The sample was determined through Proportionate Stratified Random Sampling with the Slovin formula. This quantitative study employed a causal design and used Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 4.0. Results: The results showed that field work practice and career guidance had a positive and significant effect on students’ work readiness, both directly and indirectly through self-efficacy. Self-efficacy served as a mediating variable that strengthened the relationship between both field work practice and career guidance on work readiness. Among all variables, career guidance had the strongest direct and indirect influence. Research Contributions: This research contributes to enriching theoretical understanding of the relationship between fieldwork practice, career guidance, and self-efficacy in the context of vocational education. These findings offer valuable insights for policymakers, educators, and vocational institutions in designing effective fieldwork practice programs and career guidance services that not only enhance technical skills but also build students' confidence and readiness for the workforce